IDENTIFICATION OF MULTIPLE LEAF RUST RESISTANCE GENES IN SELECTED GERMPLASM OF PAKISTANI BREAD WHEAT USING MOLECULAR MARKERS - Inamullah; T. Mahmood; H. Mahmood; H. Khan; F. U. Khan; A. Ali; M. Islam (Journal of Animal and Plant Sciences, 2020)
Leaf rust, caused by Puccinia triticina f. sp. tritici, is the most prevalent disease of wheat in Pakistan. Host resistance is the most effective and economical method of controlling the disease. In the present study, 254 Pakistani wheat germplasm were screened for the presence or absence of 17 leaf rust resistance (Lr) genes. Lr 09, 10, 20, 24, 25, 27, 28, 29, 35, 37, 39, 46, 47, 50, 51, 58 and Lr 61 were detected either as pyramided triplet and doublet genes, or as a single gene harbored varieties/germplasm. Triple and double gene pyramids were detected in 9 and 50 varieties/germplasm, respectively, while single Lr genes were detected in 29 varieties/germplasm. Genotype 10731, having the Lr28/Lr35 combination, was the leading one with highest grain yield of 20.62 g/plant. Other leading germplasm were 10754, 10767 and 10758, having combinations of Lr28/Lr35, Lr28/Lr29 and Lr25/Lr27, and grain yield of 18.84, 16.63 and 15.65, respectively. Ata Habib, with triplet pyramid of Lr27/Lr50/Lr51, was the leading cultivar with 12g/plant grain yield. Identification of Lr genes in Pakistani wheat germplasm will help accelerate the current programs of breeding for resistance to leaf rust in the varieties/germplasm of interest.
Keywords: Leaf rust; Puccinia triticina; germplasm; Lr genes; PCR; Wheat; MAS